SWOT ANALYSIS BUSINESS FEASIBILITY STUDY (CASE STUDY : ITALIAN RESTAURANT) - Febryola Indra; Verenia Novelia Christabel; Amanda Vania; Juliana Juliana (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2022)
The culinary business is one of the businesses that is in great demand by the public. This is also supported by the development and changes in lifestyle patterns. Food and beverage is indeed one of the basic needs needed by everyone, but besides that, basic needs can be said to be one of the values of today's lifestyle. Torcheat is one of the industries engaged in culinary tourism by providing all food through torch / baked cooking techniques. The menu provided will start from appetizer to dessert and beverage. This business feasibility study is intended to analyze all aspects and factors that support and influence Torcheat. In addition to collecting information in a primary manner, namely through several data sources such as books, websites and research reports. The authors also collected secondary data by distributing questionnaires and obtaining 154 respondents. The author also conducted validity and reliability tests aimed at testing the accurate level of data results obtained through the dissemination of questionnaires. By carrying out several tests and analyzing all the factors concerned. Torcheat has become more detailed, accurate, and mature conceptual.